2014
DOI: 10.2147/ijnrd.s59937
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Tego needlefree connector is associated with reduced incidence of catheter-related bloodstream infections in hemodialysis patients

Abstract: Background and objectivesCatheter-related bloodstream infections (CRBSIs) are common in hemodialysis patients using central venous catheters, and catheter occlusion also occurs frequently. The Tego needlefree connector was developed to reduce the incidence of these complications; however, existing studies of its effectiveness and safety are limited.Materials and methodsThis retrospective analysis compared outcomes among patients of a large dialysis organization receiving in-center hemodialysis using a central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The first was a small study in which bloodstream infection rates did not statistically differ between neutral-valve connector with saline lock and standard catheter caps locked with citrate (concentration 46.7%) (48). The second study was a large, retrospective trial that reported a small reduction in the use of intravenous antibiotics with the neutral-valve connector, but no difference in bloodstream infection rates (49).…”
Section: Interventions Targeting the Catheter Hub And Lumen Hub Devicesmentioning
confidence: 99%
“…The first was a small study in which bloodstream infection rates did not statistically differ between neutral-valve connector with saline lock and standard catheter caps locked with citrate (concentration 46.7%) (48). The second study was a large, retrospective trial that reported a small reduction in the use of intravenous antibiotics with the neutral-valve connector, but no difference in bloodstream infection rates (49).…”
Section: Interventions Targeting the Catheter Hub And Lumen Hub Devicesmentioning
confidence: 99%
“…The TEGO needleless connector system (Victus Inc., Miami, FL, USA) was designed to decrease catheter hub manipulation and minimize contamination via the use of a silicone barrier system. 39 Attachment to blood tubing creates a straight, internal fluid path and reinforces a closed system that avoids the need to cap and recap catheter ports. This apparatus was also designed to obviate the need for heparin-locking solution as an anticoagulant.…”
Section: Protective Barriersmentioning
confidence: 99%
“…6 Tego was previously evaluated in a retrospective study, which concluded that Tego may reduce the risk of CRBSI. 7 For additional protection, Curos is used with Tego. Curos kills organisms on the outside surface of Tego using 70% isopropanol alcohol.…”
mentioning
confidence: 99%